Widespread Structural and Functional Connectivity Changes in Amyotrophic Lateral Sclerosis: Insights from Advanced Neuroimaging Research. (10th June 2012) - Trojsi, Francesca; Monsurrò, Maria Rosaria; Esposito, Fabrizio; Tedeschi, Gioacchino
Abstract : Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disease principally affecting motor neurons. Besides motor symptoms, a subset of patients develop cognitive disturbances or even frontotemporal dementia (FTD), indicating that ALS may also involve extramotor brain regions. Both neuropathological and neuroimaging findings have provided further insight on the widespread effect of the neurodegeneration on brain connectivity and the underlying neurobiology of motor neurons degeneration. However, associated effects on motor and extramotor brain networks are largely unknown. Particularly, neuropathological findings suggest that ALS not only affects the frontotemporal network but rather is part of a wide clinicopathological spectrum of brain disorders known as TAR-DNA binding protein 43 (TDP-43) proteinopathies. This paper reviews the current state of knowledge concerning the neuropsychological and neuropathological sequelae of TDP-43 proteinopathies, with special focus on the neuroimaging findings associated with cognitive change in ALS.